Rancang Bangun Sistem Smart Dumbbell Berbasis IOT untuk Menghitung Repetisi Latihan Bicep Curl - Ibnu, Muhazrin; Al-Khowarizmi (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
The rapid development of Internet of Things (IoT) technology has opened opportunities for innovation in various fields, including fitness. This research designs and develops an IoT-based Smart Dumbbell system that automatically counts bicep curl repetitions and displays the data in real-time through a web-based monitoring platform. The system uses an ESP32 microcontroller as the main data processor, an MPU6050 sensor to detect acceleration and rotation movements, and a buzzer as an audio indicator to provide immediate feedback to users. The calculated data is sent to the Firebase Realtime Database and accessed via a website with a simple and informative interface. Testing results show that this Smart Dumbbell prototype can count exercise repetitions with an average accuracy of 87% and a minimal error compared to manual counting. The Wi-Fi connectivity runs stably, enabling real-time data transmission, and the device has a power endurance of up to ±5 hours using a 5000 mAh power bank. This system has proven effective in supporting independent workouts that are more measurable and data-driven, making it a practical and innovative solution for IoT applications in the fitness field.